2016
DOI: 10.14797/mdcj-12-1-14
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Multivessel Coronary Surgery and Hybrid Coronary Revascularization: Can We Routinely Achieve Less Invasive Coronary Surgery?

Abstract: Editor's Note: We are pleased to offer 1 credit of Continuing Medical Education for successfully completing an online quiz about this article. You may access the quiz at www.houstonmethodist.org/cme-online. AbstractCoronary artery bypass grafting (CABG) is the gold standard in managing severe coronary artery disease. However, it is associated with prolonged recovery and potential complications, in part due to the invasiveness of the procedure. Less invasive CABG techniques attempt to improve the quality and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
0
21
1
6
Order By: Relevance
“…The usage of ONCABG or peripheral pump assistance helped in keeping the mortality low in patients with poor LV function, as it prevented emergency conversions to cardiopulmonary bypass. 1,11 Mortality was very low in our study both in hospital, and at 30 days and 36 months. Majority of the patients were extubated in the operating room with the intention of fast-tracking, and time spent on the ventilator was very short resulting in an ultrashort ICU stay.…”
Section: Discussioncontrasting
confidence: 43%
“…The usage of ONCABG or peripheral pump assistance helped in keeping the mortality low in patients with poor LV function, as it prevented emergency conversions to cardiopulmonary bypass. 1,11 Mortality was very low in our study both in hospital, and at 30 days and 36 months. Majority of the patients were extubated in the operating room with the intention of fast-tracking, and time spent on the ventilator was very short resulting in an ultrashort ICU stay.…”
Section: Discussioncontrasting
confidence: 43%
“…However, limited incisions are being increasingly used in minimally invasive multivessel coronary artery revascularizations. [1][2][3][4][5] Despite the advantages in the patient's recovery, the main limitations of these minimally invasive coronary artery revascularization techniques had been the technical difficulties, longevity of the procedures, complex technology, long learning curve, and selection of patients. [6][7][8][9] Since July 2017 we started to perform multivessel coronary artery bypass grafting (CABG) routinely through the left anterior minithoracotomy in all patients.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced pulmonary function may not seem ideal for a thoracotomy approach, but other studies have shown a trend favoring thoracotomy over sternotomy. [11][12][13] We found an improvement in pulmonary function testing during immediate and late postoperative periods. 14 Other collogues have outlines bilateral internal mammary artery harvesting and outcomes from MICS CABG approach for arterial conduits.…”
Section: Discussionmentioning
confidence: 63%